2004
DOI: 10.1021/bi036256+
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β-Dependent Phosphorylation of the αNAC Coactivator Regulates Its Nuclear Translocation and Proteasome-Mediated Degradation

Abstract: c-Jun is an immediate-early gene whose degradation by the proteasome pathway is required for an efficient transactivation. In this report, we demonstrated that the c-Jun coactivator, nascent polypeptide associated complex and coactivator alpha (alphaNAC) was also a target for degradation by the 26S proteasome. The proteasome inhibitor lactacystin increased the metabolic stability of alphaNAC in vivo, and lactacystin, MG-132, or epoxomicin treatment of cells induced nuclear translocation of alphaNAC. We have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…45 Therefore, another possible and specific mediator of aNAC degradation could be GSK-3b; aNAC is a target for degradation by the 26S proteasome, which is regulated by GSK3b-dependent phosphorylation. 28 Indeed, this study demonstrated that hypoxic stress was associated with dephosphorylation of GSK-3b and that the inhibition of GSK-3b by lithium ions prevented dephosphorylation of GSK-3b and downregulation of aNAC, which rescued the hypoxic cells from apoptosis ( Figure 6). GSK-3b phosphorylates proteins at serine or threonine residues that are located 4 amino acids N-terminal to another phosphoserine (priming phosphorylation), which is introduced by other protein kinases.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…45 Therefore, another possible and specific mediator of aNAC degradation could be GSK-3b; aNAC is a target for degradation by the 26S proteasome, which is regulated by GSK3b-dependent phosphorylation. 28 Indeed, this study demonstrated that hypoxic stress was associated with dephosphorylation of GSK-3b and that the inhibition of GSK-3b by lithium ions prevented dephosphorylation of GSK-3b and downregulation of aNAC, which rescued the hypoxic cells from apoptosis ( Figure 6). GSK-3b phosphorylates proteins at serine or threonine residues that are located 4 amino acids N-terminal to another phosphoserine (priming phosphorylation), which is introduced by other protein kinases.…”
Section: Discussionmentioning
confidence: 71%
“…27 A recent study has shown that GSK-3b can phosphorylate aNAC and that the GSK-3b-dependent phosphorylation of aNAC stimulated aNAC degradation. 28 Therefore, we tested the possibility that the prevention of aNAC degradation by the inhibition of GSK-3b might rescue the hypoxic cells from apoptosis. We found that GSK-3b activation and aNAC degradation coincided in hypoxic SK-N-SH cells (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to acting as a protein translation chaperone, NACA also functions as a transcriptional coactivator in conjunction with an acidic activator (28,29). NACA may be phosphorylated by several kinases in vitro and its function as a transcriptional coactivator is regulated by phosphorylation change (30,31). Findings of the present study have shown that the phosphorylation level of NACA was not altered in the inflammatory pain model compared to the control, but that EA treatment increased the phosphorylation level.…”
mentioning
confidence: 44%
“…Papachristou et al showed that αNAC was expressed in osteosarcoma, but not in normal bone, and was expressed more strongly in high grade tumors compared with low grade tumors on immunohistochemical analysis (31). αNAC is involved in a coactivator potentiating c-Jun-mediated transcription process (20,33,34). Oya et al have reported that activation of C-Jun is acquired during aberrant proliferation of RCC (30).…”
Section: Referencesmentioning
confidence: 99%